Politeness Strategies and Factors in the Animated Movie Onward - Windi Oktaviarni Ananda; Rosnija, Eni; Wardah (Lembaga Dongan Dosen, 2025)
This research study analyzes the politeness strategies employed by the characters in the animated movie Onward and explores the factors that influence their choices. By utilizing the theories of politeness strategies proposed by Brown and Levinson, the data obtained in this qualitative research is examined. The research employs observation and note-taking techniques, using video recordings of the movie, transcriptions of the characters' utterances, and tables or data sheets as the primary tools for data collection. The findings reveal that the characters utilize four main types of politeness strategies, including bald on-record, off-record, and negative politeness, with positive politeness emerging as the dominant approach. This means that the characters prioritize maintaining social harmony in their interactions. Additionally, the factors influencing the choice of politeness strategies relevance, circumstances, and payoff were identified, with payoff indicating the primary factors that the characters aim to maximize the benefits of their conversations. Furthermore, the characters' linguistic choices were found to be influenced by the socio-cultural aspects of their society.